The Nature Of Iatrogenic Crimes And The Possibility Of Their Transformation. - D.J, Suyunova (Journal of Neonatal Surgery, 2025)
The article analyzes the current criminal legal aspects of iatrogenic crimes in modern legal science. Particularly assessed is criminal legislation, which does not specifically indicate responsibility for independent crimes committed by medical workers. The national legislation of Uzbekistan is being studied regarding the protection of the health of citizens, criminal liability for medical errors that resulted in harm to health or death of a person, the objective side of which contains elements of iatrogenic crimes. A study of the empirical base has established that crimes committed by doctors in the classical form of arrogance or negligence are not limited to careless guilt; in many cases, criminal intent is established when the perpetrators are aware of the socially dangerous nature of their act and want harmful consequences to occur. At the same time, violation of professional duties by medical workers is often combined with other crimesresponsibilities to the full extent must be assessed as iatrogenic crimes. Based on modern judicial and investigative practice, issues of pharmaceutical workers belonging to the subjects of iatrogenic crimes are raised, since the specifics of their activities are related to the protection of the life and health of citizens. It is proposed to improve national criminal legislation, provide an independent chapter on liability for iatrogenic crimes of healthcare and pharmaceutical workers, indicating a specific form of guilt, modify the fundamentals of medical law, criminal legal disciplines, and develop a methodology for investigating iatrogenic crimes.